Cultivating a Culture of Innovation: The Impact of Leadership Style on Employee Well-being and Organizational Creativity - Zhang, Yang (International Journal of Global Economics and Management, 2024)
This article delves into the intricate relationship between leadership styles, employee well-being, and organizational creativity, emphasizing the pivotal role of leadership in cultivating an innovation-driven culture. The study begins with an exploration of various leadership theories pertinent to innovation, linking these styles to the multifaceted concept of employee well-being and its influence on creative output. The research highlights how different leadership approaches—ranging from autocratic and democratic to transformational and servant leadership—impact the innovation process and employee morale. By drawing upon empirical data and case studies, the study illustrates the direct correlation between a leader's style, the well-being of their team, and the resulting innovative capacity of the organization. It further discusses strategies for leaders to foster an environment conducive to creativity and well-being, underscoring the significance of a supportive leadership approach in the modern corporate landscape. The article concludes with actionable insights and future trends, providing a roadmap for leaders and organizations aspiring to harness the full potential of their workforce in driving innovation.